Psychological Processes of Postpartum Mothers with Newborns Admitted to the Intensive Care Unit - Chiu-Kuei Lee; Xuan-Yi Huang (Elsevier, 2022)
Summary: Purpose: This research aims to explore the psychological processes of postpartum mothers during the admission of their newborns to the intensive care unit. It is hoped that the findings from this study will serve as a reference for clinical medical staff in providing individual and holistic patient care. Methods: Using grounded theory methodology, we collected data through semistructured, one-to-one in-depth interviews. When data saturation occurred, 12 participants were involved through the constant comparative analysis process. Results: The psychological processes consisted of a core category and three main categories. The core category was "worrying about the baby and striving to fulfill maternal responsibilities." The three main categories were as follows: "impact on the maternal role," "recognition of the maternal identity," and "exhibition of maternal role." The entire process may be affected by intrinsic and extrinsic factors, such as breast milk supply, timing of skin-to-skin contact, seriousness of the newborn's health conditions, the support system, and the style of postpartum confinement care. Conclusion: It is recommended that the neonatal intensive care unit should adopt family-centered care, taking an initiative to empathize and care for the mother, assisting skin-to-skin contact for the mother and baby as soon as possible, maintaining established breastfeeding, providing the correct concept of postpartum care, and encouraging participation in support groups. These activities can reduce the impact of the situation on the maternal role and improve maternal identity recognition.